Histological Evaluation of Polyacid-Modified Composite Resin and Conventional Composite Resin Used for Primary Molars Restoration - Omar A. El Meligy; Hisham I. Othman; Shahad N. Abudawood; Amani A. Al Tuwirqi; Madawi Faisal Alkeheli; Tarek R. Abdelrehim; Dalia M. Talaat (MDPI AG, 2024)
Background: The present study evaluated the histological outcomes of two dental restorative materials, polyacid-modified composite resin (compomer) and conventional composite resin, in the primary molars of puppies. Materials and Methods: Twenty sound primary molars in four puppies were used. The puppies were rendered unconscious using general anesthesia. Similar cylindrical Class V cavities were prepared in 16 of the 20 selected primary molars. The teeth were divided into three groups: Group I: Eight cavities were restored with compomer; Group II: Eight cavities were restored with conventional composite resin; Group III: Four teeth remained untreated and were used as controls. In Groups I and II, four teeth were examined histologically after 2 weeks and the other four after 6 weeks. The histological findings were analyzed and compared to determine the effects of each type of resin material on the dentine and the pulp. Results: At 6 weeks, the specimens tested for compomer showed obvious destructive changes in the central region and the region of the pulp adjacent to the cavity. The specimens tested for conventional composite resin revealed, at 6 weeks, massive destruction of the pulp tissues and abscess formation was observed. All the specimens tested in the control group showed normal cellularity, normal vascularity, and proper alignment of odontoblast cells. Conclusions: The teeth restored with compomer demonstrated more favorable pulpal reactions when compared with the teeth restored with conventional composite resin after 6 weeks.